Lycopene Rich Drink: Consumers Acceptance and Purchase Intention in Malaysia - Rawaida Rusli; Siti 'Aisyah Baharudin; Nur Fazliana Md.Noh; Mohamad Nazim Anvarali; Hadijah Hassan (Universitas Ahmad Dahlan, 2021)
This study had been carried out to assess the level of acceptance and purchase intention towards new functional beverages developed by the Malaysia Agricultural Research Development Institute (MARDI). The Lycopene Rich Drink (LRD) had been assessed towards 400 respondents in 4 Zone in Malaysia which is Northern, Southern, Western, and Eastern using stratified sampling. The results revealed that the consumers had well accepted the LRD based on the highest mean score acceptance (mean=4.16) compared to the commercial (mean=3.15) beverages in the market. Taste and color are the most preferred attributes that influenced the purchase intention. The logistic regression analysis had predicted almost 95% of the respondents' intent to purchase. Marital status and number of households are the sociodemographic factors that show a significant relationship based on the Chi-Square analysis. The findings of this study are beneficial for the beverages industry players towards exploiting the opportunity of health additional benefit offered.Â